2022
DOI: 10.1155/2022/5472105
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Optimization of Multi-UAVs for Marine Target Tracking during Approaching Stage

Abstract: This paper focuses on a coordinated tracking planning method of multiple unmanned aerial vehicles (UAVs), which was deployed in the best positions to better fulfill the marine target localization tasks when approaching the target. The optimal planning of multi-UAVs was implemented using an online centralized nonlinear model predictive control (NMPC) based on the target state’s uncertainty criteria. The penalty function is used to solve UAV platform dynamic performance in the model predictive control method to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Tuning gains of vertical and yaw controls, i.e., k V h and k Ψ, made it possible to reduce that distortion. Based on Figures 11,12,15,16,20 and 21, it can be stated that values of these gains equal to about 0.5 eliminate or reduce the overregulation significantly. Observing the impact of V max on flight trajectories in all cases of reference trajectory shape, it can be concluded that the maximum relative speed does not have to be greater than the speed of the tracked point.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tuning gains of vertical and yaw controls, i.e., k V h and k Ψ, made it possible to reduce that distortion. Based on Figures 11,12,15,16,20 and 21, it can be stated that values of these gains equal to about 0.5 eliminate or reduce the overregulation significantly. Observing the impact of V max on flight trajectories in all cases of reference trajectory shape, it can be concluded that the maximum relative speed does not have to be greater than the speed of the tracked point.…”
Section: Discussionmentioning
confidence: 98%
“…The present work presents a method that applies an artificial-potential-field approach and modified flight control for quadcopters to achieve the tracking of a freely moving point with unknown dynamics. Thus, in such conditions, MPC (model predictive control) [ 15 ] or Kalman filter [ 16 ] based methods cannot be applied, because the estimation or prediction of the target’s movement within the time horizon is not possible, or the model of the target is not similar to the UAV in contrast to [ 17 ], where sliding mode control is applied. The proposed method can also be used in applications where a virtual moving point is controlled by a ground station to achieve complex shapes of trajectories with the use of any local positioning system.…”
Section: Introductionmentioning
confidence: 99%